The affluency to quit: How inheritances affect retirement plannings - Tobias L. Crusius; Marten von Werder (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2017)
This study uses the German SAVE panel study in order to estimate the effect of intergenerational transfers on the expected retirement entry age of individuals. The literature in this field typically estimates the transfer effect on the actual retirement probability. We suggest to base the analysis on the expected retirement age instead. This entails two methodological advantages: First, it is possible to exploit the within individual variation for the entire sample (even of those who do not retire) and thereby permits to analyze the life-cycle considerations of younger age groups. Second, the effect size can easily be expressed in terms of time and thereby monetary opportunity costs. We find that heirs expect to retire earlier, even when receipts are expected to some degree. Specifically, heirs plan to retire four to five months earlier and thereby accept costs in the form of foregone income and pension entitlements corresponding to 20-30% of the inheritance.
Keywords: 330